Model of Internalizing Religious Moderation: A Study of Muhammadiyah Elite Preaching in Surabaya - tualeka, wahid (TA`DIBUNA, 2025)
Abstract In the context of religious life in Indonesia, religious moderation has become a highly relevant theme, particularly amid the growing challenges of radicalization and social conflict. This study aims to explore the model of internalizing religious moderation through an examination of the preaching practices of Muhammadiyah elites in Surabaya. Using a qualitative approach, the study analyzes the strategies and narratives of preaching oriented toward the values of moderation and tolerance promoted by Muhammadiyah figures. The findings indicate that the preaching conducted by Muhammadiyah elites in Surabaya plays a significant role in shaping public understanding of religious moderation and in mitigating potential interfaith conflicts. These findings are expected to contribute to the development of more inclusive and effective preaching strategies in promoting religious moderation in Indonesia.